Impact of quantitative safety targets on road fatality reduction: an empirical support toward governance plan - Haizhou Cui; Yuliang Guo; Yuchen Li; Jianwei Zhang; Yida Wang; Lin Yang; Jiayi Hu; Hak Kei Wong; Yuxuan Bai; Yang Ma; Faan Chen (Frontiers Media S.A., 2023)
IntroductionThe role of quantitative target setting has become an important topic in debates on the improvement of road safety performance. Specifically, there are questions regarding the relationship between quantitative safety targets and their actual effects. Although previous studies have provided important insights into this subject, their empirical findings have largely been equivocal, and research on this topic remains inadequate.MethodsBased on panel data representing 20 years of observations from 34 OECD member states, we employed nonlinear and linear panel models to investigate whether and how the attributes of quantitative road safety targets (i.e., target ambition and duration) influence their success (i.e., target completion status and rate).ResultsThe results indicate that a quantitative target with a higher level of ambition is associated with a lower likelihood and rate of completion, whereas there is no support for a connection between target duration and final completion rate. This suggests that an excessively ambitious target does not necessarily result in better road safety performance and is detrimental to achieving expected fatality reductions.ConclusionFrom an empirical perspective, this study revealed a potential interaction effect between quantitative road safety targets and practical fatality reduction performance, providing government officials and policymakers with essential references for future practices on target setting and governance planning in regard to public health.